2021
DOI: 10.1002/jssc.202100343
|View full text |Cite
|
Sign up to set email alerts
|

Enantioseparation of phenethylamines by using high‐performance liquid chromatography column permanently coated with methylated β‐cyclodextrin

Abstract: Cyclodextrins and their derivatives have been used for chiral high‐performance liquid chromatography selectors, while they are costly to use as mobile phase additives in high‐performance liquid chromatography. Here, we report application of phenyl column coated permanently with methylated β‐cyclodextrin for chiral high‐performance liquid chromatography. A 0.1% (v/v) phosphoric acid solution containing 1 M NaCl and 0.5% (w/v) methylated β‐cyclodextrin was subjected to a phenyl column at a flow rate of 0.5 mL/mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
0
4
0
1
Order By: Relevance
“…Compared with the additive of 2,6di-O-methyl-β-CD, the CSP of 2,6-di-O-methyl-β-CD gave better HPLC enantio-separation performance for four phenethylamine enantiomers, indicating the greater efficiency of CSP in chiral HPLC. 10 3,5-Dichloro-phenylcarbamated mono-6-ethylenediamine-β-CD was covalently anchored on silica particles to achieve HPLC enantio-separation of proton pump inhibitors. 11 To reduce the steps for the preparation of CD-based CSPs, Wang et al 12 strategy to prepare anhydride-linked β-CD-bonded silica as the CSP for HPLC and obtained baseline separation of 17 kinds of enantiomers.…”
Section: ■ Chromatographymentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with the additive of 2,6di-O-methyl-β-CD, the CSP of 2,6-di-O-methyl-β-CD gave better HPLC enantio-separation performance for four phenethylamine enantiomers, indicating the greater efficiency of CSP in chiral HPLC. 10 3,5-Dichloro-phenylcarbamated mono-6-ethylenediamine-β-CD was covalently anchored on silica particles to achieve HPLC enantio-separation of proton pump inhibitors. 11 To reduce the steps for the preparation of CD-based CSPs, Wang et al 12 strategy to prepare anhydride-linked β-CD-bonded silica as the CSP for HPLC and obtained baseline separation of 17 kinds of enantiomers.…”
Section: ■ Chromatographymentioning
confidence: 99%
“…For example, 2-hydroxypropyl-β-cyclodextrin (HP-β-CD) and carboxy methyl-β-cyclodextrin (CM-β-CD) served as mobile-phase additives for baseline separation of mandelic acid derivatives and basic drug enantiomers on achiral C18 HPLC column, respectively. , More CD derivative-based composites were fabricated as CSPs for chiral HPLC. Compared with the additive of 2,6-di-O-methyl-β-CD, the CSP of 2,6-di-O-methyl-β-CD gave better HPLC enantio-separation performance for four phenethylamine enantiomers, indicating the greater efficiency of CSP in chiral HPLC . 3,5-Dichloro-phenylcarbamated mono-6-ethylenediamine-β-CD was covalently anchored on silica particles to achieve HPLC enantio-separation of proton pump inhibitors .…”
Section: Chromatographymentioning
confidence: 99%
“…Z tego względu kompleksowanie związków jest procesem stereoselektywnym, dlatego też mogą oddziaływać silniej z jednym z enancjomerów i tym samym mogą być wykorzystywane do rozdzielania mieszaniny racemicznej [22,23]. Ta właściwość cyklodekstryn i ich pochodnych sprawiła, że znalazły one zastosowanie jako wypełniacze do kolumn wysokosprawnej chromatografii cieczowej (HPLC), chromatografii gazowej (GC), są również stosowane w chiralnej elektroforezie kapilarnej (CCE) i wielu innych metodach analitycznych [24,25]. Co ciekawe, chiralne cząsteczki mogą wiązać się również z zewnętrzną powierzchnią pierścienia.…”
Section: Rysunek 1 Wzór Strukturalny β-Cyklodekstryny [9]unclassified
“…Then, CDs and chiral analytes with a hydrophobic group can form the inclusion complexes in solution under dynamic equilibrium [17][18][19][20]. Recently, we enantioseparated mandelic acid [21] and phenethylamines [22] by HPLC with a phenyl column and mobile phases precoated with hydroxypropyl-β-CD and methylated β-CD, respectively. The two CDs were adsorbed on a phenyl column, which suggested that a phenyl column precoated with hydroxypropyl-β-CD or methylated β-CD could act as a transient chiral column.…”
Section: Introductionmentioning
confidence: 99%